Smart Management of Malnutrition Using Local Foods: A Sustainable Initiative for Developing Countries - Amadou, Issoufou; Lawali, Sitou (Frontiers in Sustainable Food Systems, 2022)
For One of the major challenges currently facing the developing world, whether it is cause by climate change, terrorism and conflict or demographic shifts. Poverty is the main cause of malnutrition in this part of world, and no progress is possible without the alleviation of poverty to reduce malnutrition. Reducing household vulnerability and increasing their resilience are pathway to sustainable malnutrition management. Malnutrition been a major threat to the health and development of children in developing countries, with high levels of micronutrient deficiencies, stunting and global acute malnutrition. The rates of malnutrition of all forms are above the thresholds accepted by the WHO in some regions. To this end, the resilience program on nutrition in a developing country through the activity of learning home for nutritional rehabilitation and dietary promotion known as FARN in this case was characterized by successful results. either for the statements of beneficiaries and those of non-beneficiaries, on the reduction and management of malnutrition in their health centers. The FARN is like “Give a man a fish and you feed him for a day. Teach a man to fish and you feed him for a lifetime” to the vulnerable people; thus, the mothers' knowledge on the child's nutritional status and the use of local based foods diets showed improvement as the fact of impact of resilience program implemented. The package of activities on resilience nutrition security in the developing countries introduced through the humanitarian organizations intervention that are the United States Organizations and NGOs with their implementation partners was a success with very significant impacts that have changed considerably the living status of households. Reduction of malnutrition in most families despite their vulnerabilities are now shown in the communities. The impacts of such approach of development increase the standard of living of the population. It was revealed that the development of a community contribution initiative to support activity through FARN in the rural areas in a developing country have enabled Income Generating Activities (IGA) by the participating community; thus, this means having sustainable malnutrition management.